Simulation-based learning and digital tools. A trial for Pharmacy Services - Fabrizio Bracco; Maria Carola Morozzo della Rocca; Federica Delprino; Silvia Pregaglia (Agathón)
This paper focuses, amidst a collective desire to re-appropriate sociality and a focus on the use of digital and ‘phygital’ practices to promote inclusion and diminish the human impact on the planet, on the choice of hybrid, physical or virtual modes of interaction as a function of punctual rather than generalised needs to foster a conscious and sustained digital transition in university education. The essay deals with the simulation method as an established tool in learning medical disciplines, declining it in an unprecedented scenario such as pharmaceuticals and experimenting with its digitisation. With a view to the development of integrated didactics between analogue and digital, the case study Pharmacy of Services provides the basis for an extended reflection on the future potential of university education.